Growth performance and expression of immune‐regulatory genes in rainbow trout (Oncorhynchus mykiss) juveniles fed extruded diets with varying levels of lupin (Lupinus albus), peas (Pisum sativum) and rapeseed (Brassica napus). (8th June 2012) - Hernández, A.J.; Román, D.; Hooft, J.; Cofre, C.; Cepeda, V.; Vidal, R.
Abstract Varying levels of lupin (Lupinus albus), peas (Pisum sativum) and rapeseed (Brassica napus) meals were evaluated as partial replacements for fishmeal in extruded diets for rainbow trout, with particular emphasis on the effect on growth performance and the expression of three genes associated with immune response. A series of 10 isonitrogenous (450 g kg−1 crude protein) and isolipidic (17 g kg−1 crude lipid) diets were formulated to contain different levels of lupin (150 g kg−1, 250 g kg−1 and 350 g kg−1), rapeseed cake (100 g kg−1, 200 g kg−1 and 300 g kg−1) and pea (50 g kg−1, 150 g kg−1 and 250 g kg−1) meals. The control diet was prepared with fish meal as the sole source of protein. Triplicate groups of fish (37.08 ± 3.58 g) were assigned to each experimental diet. The feeding experiment was conducted for 9 weeks at 14.3 ± 0.4 °C. The fish were hand fed three times per day, 6 days per week to apparent satiation level. Growth performance, feed utilization and immunological response were significantly affected by the type of plant protein as well as level of inclusion. Hepatosomatic index (HSI) increased in all groups of fish fed diets with pea and rapeseed cake meal. Dietary inclusion of lupin did not affect the expression of Mx‐1 gene. Our results suggest that fish meal can be replaced by lupin in the diet of rainbow trout without any apparent adverse effects on key innate immunological genes.